Morphology of the EGG of Sarcodexia lambens (Diptera: sarcophagidae) Morfologia do ovo de Sarcodexia lambens (Diptera: sarcophagidae) - Hugo de Souza Lopes; Antônio Cesar Rios Leite (Memorias do Instituto Oswaldo Cruz, 1989)
The egg of Sarcodexia lambens (Diptera: Sarcophagidae) is described on the basis of scanning electron microscopy. O ovo de Sarcodexia lambens (Diptera: Sarcophagidae) é descrito a nível de microscopia eletrônica de varredura.